Umbilical Hernia Containing the Ileocecal Appendix - Ines Teixeira (Portuguese Journal of Pediatrics, 2020)
Umbilical hernia is a common finding in children. Complicated umbilical hernias are rare and only a few cases of ileocecal appendix incarceration or strangulation in umbilical defects were described in literature. In this article, we present a case of a four-year-old girl with an asymptomatic and uncomplicated proboscoid umbilical hernia submitted to elective repair in ambulatory setting. During surgery, the ileocecal appendix was found trapped in the umbilical defect, showing signs of mild congestion. The anatomopathological exam confirmed the mucosal lymphoid hyperplasia and congested wall of the appendix. We believe that prompt diagnosis and treatment, according to main recommendations reviewed in this article, allowed an elective repair of the hernia and prevented a probable scenario of complication as appendix incarceration.